OPTIMALISASI UJIAN SEKOLAH PRAKTIK BERBASIS LINGKUNGAN UNTUK MENANAMKAN JIWA KEWIRAUSAHAAN PESERTA DIDIK SMP NEGERI 8 BONTANG - Hj. Sukarsih (Universitas Islam Balitar, 2016)
This study is aimed at promoting school environment to teaching practice for enterpreneurship. Home industries are promoted for teaching practice objects. The study used School Action Research whose objectives are to review and evaluate school policy. Subjects of the study were 69 students of grade IX at SMPN 8 Bontang and 18 teachers three of them are science teachers. The study was conducted in January to February 2014. The findings of the study referred to UNESCO Pillars in education: learning to know, learning to do, learning to be, and learning to live together in peace and harmony. Products of the study that is “terasi– was processed by students through discovery and problem based project learning starting from finding information (learning to know), trying to make on suervisory, making by themselves (learning to be), and sale the product with school community (learning to live together). The finding probes that PAIKEM is applicable and environment is worth for teaching sources.